The impact of Customer Relationship Management (CRM) on a beer manufacturing company’s sales performance - Cele, Zibuse Ellington; Msosa, Steven Kayambazinthu; Ntshangase, Bhekabantu Alson (Management and Entrepreneurship: Trends of Development, 2023)
The shift away from an economy focused on transactions and towards one based on relationships has taken place worldwide, and this movement can be observed quite plainly in South Africa’s business environment. Individualized customer care is becoming an increasingly important factor for customers who now have higher expectations than before. Therefore, this study analysed the impact of customer relationship management (CRM) on a beer manufacturing company’s sales performance. A quantitative, cross-sectional descriptive research design was adopted to collect data from a stratified random sample of 172 liquor outlet owners within the Durban region. The respondents can be categorised as retailers, distributors, On-Con and Off-Con. The findings show that customers were generally satisfied with the trading environment, order placing, delivery and information sharing. The use of data analytics and technology in general should be put at the forefront of any effective customer relationship management (CRM) solution for the firm. This might be a very helpful tool for organization in its attempts to mould its business environment to better suit the expectations of its customers and clients. This study has contributed to the literature on customer relationship management in the manufacturing sector, with specific reference to South Africa. JEL Classification: M31, M11, L66.